Arterial hypertension epidemiology in Russia; the results of 2003-2010 federal monitoring - R. G. Oganov; T. N. Timofeeva; I. E. Koltunov; V. V. Konstantinov; Yu. A. Balanova; A. V. Kapustina; I. N. Lelchuk; S. A. Shalnova; A. D. Deev (Кардиоваскулярная терапия и профилактика)
Aim. To assess the dynamics of arterial hypertension (AH) prevalence in the Russian population, patients’ awareness, treatment with antihypertensive agents (AHA), treatment effectiveness, and the determinants of the latter. Material and methods. As a part of the Federal Target Programme “Prevention and treatment of arterial hypertension in the Russian Federation”, four randomly selected population samples from various Russian regions were examined in 2003-2004, 2005-2006, 2007-2008, and 2009-2010. Results. In the Russian population, AH prevalence was 39,7%, being higher in women (40,5%) than in men (38,0%). No significant changes in AH prevalence were observed for the analysed period. Patients’ awareness was 81,1% (82,9% in women vs. 77,9% in men). AHA therapy prevalence increased from 62,6 % to 66,1%. The most widely used AHA included ACE inhibitors, diuretics, and beta-adrenoblockers; old medications were taken by 17,7% of the patients only. Conclusion. AH prevalence in the Russian population was 39,7% and did not change over the recent years. However, there was an increase in the percentage of patients taking AHA, as well as in the percentage of women with effectively treated AH. In addition, the treatment with recommended AHA became more prevalent. Ineffective therapy was typically due to lower education level, alcohol abuse, or co-existing risk factors.